Quantification of Sunscreen Benzophenone-4 in Hair Shampoos by Hydrophilic Interactions Thin-Layer Chromatography/Densitometry or Derivative UV Spectrophotometry - Anna W. Sobańska; Katarzyna Kałębasiak; Jarosław Pyzowski; Elżbieta Brzezińska (Journal of Analytical Methods in Chemistry)
Benzophenone-4 (BZ4) was separated from surfactants, dyes, preservatives, and other components of hair shampoos by thin-layer chromatography on silica gel 60 stationary phase, with ethyl acetate-ethanol-water-pH 6 phosphate buffer (15 : 7 : 5 : 1 v/v/v/v) as mobile phase. Densitometry scanning of chromatograms was performed at 285 nm. The densitometric calibration curve for BZ4 was nonlinear (second-degree polynomial), with R>0.999. The limits of detection and quantification were ca. 0.03 and ca. 0.1 μg spot−1, respectively. The results obtained by HPTLC-densitometry were compared to those obtained by zero and 2nd derivative UV spectrophotometry. In the case of spectrophotometric methods, calibration curves were linear with R>0.9998. The chromatographic method was fully validated.